"In your own words, how certain are you?" Post‐identification feedback distorts verbal and numeric expressions of eyewitness confidence. Issue 6 (8th September 2021) - Kenchel, Jillian M.; Greenspan, Rachel L.; Reisberg, Daniel; Dodson, Chad S.
Summary: After making a lineup identification, eyewitnesses remember being more confident in their identification and having a better view of the initial crime if they are told they correctly identified the suspect compared to witnesses not given this feedback. The present studies investigated whether this effect of feedback occurs similarly when witnesses report their confidence numerically and when they report their confidence in their own words. Across three studies, participants ( N  = 1396) watched a mock crime video, received either confirmatory feedback or not, and reported their confidence in words, numbers, or both words and numbers. Results showed a significant effect of feedback on both confidence and witnessed experience in all confidence conditions. This effect occurred with both biased and unbiased lineup instructions and with both target‐present and target‐absent lineups. The results advance discussions about the best means for reporting confidence in the field.